Hubungan Jenis Kelamin dan Gambaran Klinis Celah Bibir Non Sindromik di CLP Center FK UMM - Asparini, Ruby Riana; Susanti, Erika Yuli; Prihanti, Gita Sekar (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2018)
Relationship between Sex and Clinical Features of Non-Syndromic Cleft Lip at CLP Center FK UMMBackground: Non-syndromic cleft lip is a type of cleft that is not accompanied by abnormalities in the head and neck. There are sex differences in the timing of palate closure.Objective: To determine the relationship between sex and clinical features of non-syndromic cleft lip (with or without cleft palate) at CLP Center FK UMM (2016-2017).Method: CrossSectional. Data on sex and clinical features of non-syndromic cleft lip were obtained from the CLP Center FK UMM as many as 241 out of 271. Data analysis used the chi-square test with conditionsexpectedcount less than five not more than 20%. If it does not meet the requirements use the non-parametric Mann Whitney test.Results: The results of the chi-square test data analysis did not meet the requirements so that a non-parametric Mann Whitney test was carried out which showed p = 0.152 (p> 0.05), which means that there is no sex relationship and clinical features of cleft lip (with or without cleft palate). ) non-syndromic.Conclusion: There is no sex relationship and the clinical picture of cleft lip (with or without cleft palate) is non-syndromic.Latar Belakang: Celah bibir non sindromik merupakan jenis celah yang tanpa disertai kelainan pada kepala dan leher. Terdapat perbedaan jenis kelamin terhadap waktu penutupan langit-langit.Tujuan: Mengetahui hubungan jenis kelamin dan gambaran klinis celah bibir (dengan atau tanpa celah langit-langit) non sindromik di CLP Center FK UMM (tahun 2016-2017). Metode:  CrossSectional. Data jenis kelamin serta gambaran klinis celah bibir non sindromik yang diperoleh dari CLP Center FK UMM sebanyak 241 dari 271. Analisis data menggunakan uji chi-Squaredengan syaratexpectedcountkurang dari lima tidak lebih dari 20%. Jika tidak memenuhi syarat menggunakan uji non parametrikMann Whitney.Hasil: Hasil analisis data uji chi-Squaretidak memenuhi syarat sehingga dilakukan uji non parametrikMann Whitney yang menunjukkan p=0,152 (p>0,05), yang berarti tidak ada hubungan jenis kelamin dan gambaran klinis celah bibir (dengan atau tanpa celah langit-langit) non sindromik.Kesimpulan: Tidak terdapat hubungan jenis kelamin dan gambaran klinis celah bibir (dengan atau tanpa celah langit-langit) non sindromik.